2013
DOI: 10.1016/j.talanta.2013.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating specificity of sequential extraction for chemical forms of lead in artificially-contaminated and field-contaminated soils

Abstract: In the present study, we evaluate a commonly employed a modified Bureau Communautaire de Référence (BCR test) 3-step sequential extraction procedure for its ability to distinguish forms of solid-phase Pb in soils with different sources and histories of contamination. When the modified BCR test was applied to mineral soils spiked with three forms of Pb (pyromorphite, hydrocerussite and nitrate salt), the added Pb was highly susceptible to dissolution in the operationally-defined “reducible” or “oxide” fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Highly variable spatial distribution of Pb in soils of urban environments, from the scale of several hundred meters (Säumel et al, 2012; Shinn et al, 2000) to the minute scale of the root zone, soil aggregates and microscopic particles (Tai et al, 2013; Wharton et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Highly variable spatial distribution of Pb in soils of urban environments, from the scale of several hundred meters (Säumel et al, 2012; Shinn et al, 2000) to the minute scale of the root zone, soil aggregates and microscopic particles (Tai et al, 2013; Wharton et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations using the electron microprobe have revealed a strong tendency for Pb in anthropogenically contaminated soils to be spatially distributed in a highly heterogeneous manner (Cotter-Howells, 1996;Fleming et al, 2013;Tai et al, 2013;McBride, 2016). This characteristic was observed in the soils of the present study, with the EDS X-ray spectra of selected Pb-rich regions within the (Albany) urban soil and orchard soil in Figure 3 showing a clearer indication of a Pb phosphate phase in the former soil, as the Pb "peak" has greater intensity than the P "peak", consistent with the measured X-ray spectrum of pyromorphite (not shown here).…”
Section: Microprobe Results For Pb-rich Particlesmentioning
confidence: 99%
“…We used a density separation procedure to concentrate Pb-rich particles in the high-Pb urban and orchard soils, as previous investigation of contaminated orchard and urban soils had indicated that Pb tends to be concentrated in discrete particles (Tai et al, 2013).…”
Section: Electron Microprobe Investigation Of Pb-rich Particlesmentioning
confidence: 99%
“…The sequential extraction procedure, as shown in Tab. , was chosen for the optimized BCR scheme . Sequential extraction was performed for both fractions of contaminated soil: The fraction extracted by LED3A and the fraction without extraction.…”
Section: Methodsmentioning
confidence: 99%
“…At present, sequential extraction techniques are commonly used to study heavy metal behavior in soils. The BCR (formerly the Community Bureau of Reference) sequential extraction procedure is recommended by the Standards, Measurements and Testing Program of the European Commission .…”
Section: Introductionmentioning
confidence: 99%